(untitled) (Docentes 2.0 Journal, 2025)
Studies on school leadership address the effectiveness of school management and the factors associated with the quality of education, which are evidenced in learning achievements. The research objective was to determine the impact of pedagogical leadership and managerial skills on educational management in an educational network in Metropolitan Lima - 2023. The methodology presents a hypothetical-deductive method, positivist paradigm, quantitative approach, non-experimental design, correlational-causal and cross-sectional type. The sample consisted of 186 teachers from a network of public educational institutions. The technique used in this study was the survey. Three questionnaires were used to collect information about pedagogical leadership, managerial skills, and educational management in the educational institutions belonging to the network. According to the McFadden test, the statistical analysis Pseudo R-square showed that pedagogical leadership and management skills influence educational management with p = 0.000 < 0.05. It was concluded that pedagogical leadership and educational management influence 20.8% of educational management in the institutions of the educational network under study.